A study on common mistakes committed by Vietnamese learners in pronouncing English word-final consonants “l, ʃ, t, d, k, g” at Espeed English center - Tôn, Thị Thùy Dương (2020)
The specific aims of the study are: Investigate the most common mistakes when pronouncing English wordfinal consonants “l, ʃ, t, d, k, g” by Vietnamese learners at Espeed English Center. Identify the reasons for students’ problems of pronunciation. Propose possible appropriate techniques to correct their problems